2019
DOI: 10.1186/s12875-019-0999-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hazardous alcohol use among Spanish primary care providers

Abstract: Background Alcohol use by health care professionals is one of the potential factors that may affect the prevention of hazardous drinking in Primary Care (PC). The objective of the study was to estimate the prevalence of hazardous alcohol use by PC professionals and assess the existing relationship between socio-demographic and occupational variables of PC professionals and their alcohol use. Methods A descriptive, cross-sectional, observational, multicenter study was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Research has shown individuals who experience BO are likely to drink more alcohol ( Alexandrova-Karamanova et al ., 2016 ; Williams et al ., 2020 ). In addition, certain medical professions have a higher rate of hazardous alcohol use when compared with the general public ( Romero-Rodríguez et al ., 2019 ). Hazardous alcohol consumption is characterized by a volume of alcohol or pattern of alcohol use that results in an increased risk for harmful health consequences ( Effertz, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown individuals who experience BO are likely to drink more alcohol ( Alexandrova-Karamanova et al ., 2016 ; Williams et al ., 2020 ). In addition, certain medical professions have a higher rate of hazardous alcohol use when compared with the general public ( Romero-Rodríguez et al ., 2019 ). Hazardous alcohol consumption is characterized by a volume of alcohol or pattern of alcohol use that results in an increased risk for harmful health consequences ( Effertz, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies explored the health status of physicians, including primary care physicians (PCPs), because of the proven link between their health and the quality of patient care 1 – 3 . These studies focused primarily on psychiatric illness 4 11 and addiction 12 19 . We lack data regarding their physical health.…”
Section: Introductionmentioning
confidence: 99%
“…En España, una encuesta reciente entre los profesionales de la Atención Primaria mostró una mayor prevalencia del consumo de alcohol en este colectivo con respecto a la población general, con un porcentaje de consumo de riesgo según los criterios de la AUDIT-C del 32% (Romero-Rodríguez et al, 2019a). El perfil de un bebedor de riesgo en esta muestra era el de un varón, médico, mayor de 56 años y con más años promedio de carrera profesional (Romero-Rodríguez et al, 2019b).…”
unclassified